The Lack of Alternative Oxidase 1a Restricts in vivo Respiratory Activity and Stress-Related Metabolism for Leaf Osmoprotection and Redox Balancing Under Sudden Acute Water and Salt Stress in Arabidopsis thaliana - Del-Saz, Néstor F.; Iglesias-Sanchez, Ariadna; Alonso-Forn, David; López-Gómez, Miguel; Palma, Francisco; Clemente-Moreno, María José; Fernie, Alisdair R.; Ribas-Carbo, Miquel; Florez-Sarasa, Igor (Frontiers in Plant Science, 2022)
In plants salt and water stress result in an induction of respiration and accumulation of stress-related metabolites (SRMs) with osmoregulation and osmoprotection functions that benefit photosynthesis. The synthesis of SRMs may depend on an active respiratory metabolism, which can be restricted under stress by the inhibition of the cytochrome oxidase pathway (COP), thus causing an increase in the reduction level of the ubiquinone pool. However, the activity of the alternative oxidase pathway (AOP) is thought to prevent this from occurring while at the same time, dissipates excess of reducing power from the chloroplast and thereby improves photosynthetic performance. The present research is based on the hypothesis that the accumulation of SRMs under osmotic stress will be affected by changes in folial AOP activity. To test this, the oxygen isotope-fractionation technique was used to study the in vivo respiratory activities of COP and AOP in leaves of wild-type Arabidopsis thaliana plants and of aox1a mutants under sudden acute stress conditions induced by mannitol and salt treatments. Levels of leaf primary metabolites and transcripts of respiratory-related proteins were also determined in parallel to photosynthetic analyses. The lack of in vivo AOP response in the aox1a mutants coincided with a lower leaf relative water content and a decreased accumulation of crucial osmoregulators. Additionally, levels of oxidative stress-related metabolites and transcripts encoding alternative respiratory components were increased. Coordinated changes in metabolite levels, respiratory activities and photosynthetic performance highlight the contribution of the AOP in providing flexibility to carbon metabolism for the accumulation of SRMs.